Impact of Transformational Leadership on Innovation among Managerial Employees in the Banking Sector in Cambodia - Sopheak Chea; Sarom Mok; Sarin Chey; Sereyrath Em (Journal of General Education and Humanities, 2025)
Transformational leadership is recognized as a critical factor influencing creativity. This strategy should be executed to create an environment, procedure, and framework that fosters innovation in the banking sector. The current study aims to examine how transformational leadership (TL) influences product and process innovation within ACLEDA Bank Plc. in Cambodia. A total of 262 branch managers from ACLEDA Bank Plc. participated in this study, representing all branches of the bank across Cambodia. A quantitative design was employed in this study. Inspired by the Multi-Factor Leadership Questionnaire (MLQ), the first author of this study created and distributed a Transformational Leadership (TL) questionnaire. To minimize errors and ambiguity, the questionnaire forms were translated into Khmer and back-translated into English by experts, and the instruments were examined to confirm their validity by the field experts, too. The Khmer versions of the questionnaires were deployed in the field for testing, yielding a reliability coefficient of 0.93. The correlation between transformational leadership and innovation was examined using quantitative and explanatory analysis. This study employed structural equation modeling (SEM) using AMOS 20 software. The collected data were analyzed using descriptive and inferential statistics via computer software methods. The findings indicated that transformational leadership is crucial in fostering innovation within ACLEDA Bank Plc. The primary finding reached was that Intellectual Stimulation exerts minimal influence on the originality of products and processes. Individualized Consideration emerged as the foremost predictor of both aspects, succeeded by Idealized Influence and Inspirational Motivation, respectively. The study indicated that a transformational leadership style improves the overall performance of ACLEDA Bank Plc. by encouraging employee participation in creative processes and products. These findings enhance our comprehension of the mechanisms through which TL fosters creativity. Furthermore, they emphasize the benefits of generating more innovative findings and achievements.